PENILAIAN TINGKAT KESEHATAN KOPERASI DARI ASPEK LIKUIDITAS, PERMODALAN, KEMANDIRIAN DAN PERTUMBUHAN KSP SAHABAT SETIA SMAN 6 KUPANG - Avelina Felsiana Nutri; Christiana Wahyuningrum (Universitas Boyolali, 2019)
The problem in this research is fixed asset did not increase and current liabilities increased yet give description about the health level of cooperative from the aspect of liquidity, capital, independence, and growth. The formulation of the problem in this research is how the level of health of cooperative from liquidity aspect, capital aspect, and independence aspect and growth of KSP Sahabat Setia SMAN 6 Kupang. The purpose of this research is to know the level of health of cooperative from liquidity aspect, capital aspect and independence aspect and growth of KSP Sahabat Setia SMAN 6 Kupang. The required data are quantitative data and qualitative data obtained by a documentation study. The technique of data analysis in this research is quantitative descriptive analysis by using indicator from three aspects that is liquidity aspect, capital aspect, and independence aspect and growth aspect. Based on data analysis, it can be concluded that the health level of savings and loan cooperatives of SMAN 6 Kupang faithful from 2012-2016 is categorized quite healthy because the average score achieved for each aspect obtained is 25.6 where the highest score is 40. The score ranges from 20 ≤ X <30. Based on the results of the above analysis, the suggestion for the manager of KSP SahabatSetia SMAN 6 Kupang is to make improvements in the balance between cash and current liabilities so that there are no idle funds. The cash value can be minimized by providing loans to members, while current liabilities can be increased by attracting members to save at KSP Sahabat Setia SMAN 6. Managers should balance their own capital to loan capital by increasing the loan from outside in order to achieve maximum value. Managers need to increase the acquisition of SHU by optimizing assets and managing their owned capital by maximizing the participation of principal savings, mandatory savings, capitalist saving and cooperative service transactions by members. Keywords: KSP Health Level from Liquidity, Capital, Growth and Independence Aspect